Foreign investors’ perception of ESG controversies in Brazil - Ettore, Luis Antonio Gioia (2024)
We study international minority shareholders' perception of ESG controversies in the Brazilian market, focusing on Vale S.A. and JBS S.A. We analyze 1757 votes cast by international investors from 2013 to 2022. Vale S.A. received more attention from the investors, reaching 72% of the total dissenting votes. Our sample includes 54 funds managed by 28 investors. DWS Investment GmbH and the University of California are the investors most concerned with Vale S.A. and JBS S.A.'s ESG controversies. The German investor DWS Investment GmbH represents 26% (14) of the total funds and 76% of the total flow of dissenting votes. We find that foreign institutional shareholders are well-informed and engage in dissent voting against management, with detailed justification based primarily on Vale S.A. and JBS S.A.'s severely controversial ESG issues. With greater foreign scrutiny and investors engaged in challenging corporate decisions, Brazilian companies should significantly develop their governance structure by improving ESG practices and aligning minority shareholders' interests. Finally, Brazilian companies should use this learning curve window of newly adopted practices aligned with high-quality international standards, avoiding the possibility of greenwashing.